Pseudomonas aeruginosa Takes a Multi-Target Approach to Achieve Junction Breach - Golovkine, Guillaume; Reboud, Emeline; Huber, Philippe (Frontiers in Cellular and Infection Microbiology, 2018)
Pseudomonas aeruginosa is an opportunistic pathogen which uses a number of strategies to cross epithelial and endothelial barriers at cell–cell junctions. In this review, we describe how the coordinated actions of P. aeruginosa's virulence factors trigger various molecular mechanisms to disarm the junctional gate responsible for tissue integrity.